Fauna de peixes em riachos: avaliação das intervenções antrópicas sobre os atributos e estrutura funcional das assembleias - Larentis, Crislei (2015)
The present paper aimed to evaluate the functional structural of the fish fauna in streams with different land uses in their micro basin. The fish fauna was sampled in fourteen streams, belonging to four watershed, between 2006 and 2014, by electric fishing technique. The streams were categorized according to land use and occupation and the species were classified according to their functional traits. Were sampled 81 fish species distributed in different functional groups related with the tolerance to hypoxia, food use (trophic guilds), reproduction (parental care) and habitat use. Bidimensional graphics were built with the data biomass of the functional groups, showing that the groups that stood out, independent of the land use, were the omnivorous, benthics, and nonguarders species. The Monte Carlo test proved there is dependence between the functional traits and land use. The functional diversity analyses showed that the functional metrics decreased substantially as it increases the land use and occupation, mainly in urban streams. It follows that the land use exerts direct influence on functional diversity of fish species in streams.